2013
DOI: 10.1002/asia.201300930
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐ and Rhodium‐Catalyzed Dehydrogenative Silylations of C(sp3)H Bonds Adjacent to a Nitrogen Atom Using Hydrosilanes

Abstract: Now that is just silylated: In the presence of iridium or rhodium catalysts, C(sp3)H bonds adjacent to a nitrogen atom were silylated by the aid of a pyridine‐directing group. In iridium catalysis, a hydrogen‐trapping reagent such as norbornene or tert‐butylethylene, which is usually required in late transition‐metal‐catalyzed dehydrogenative coupling reactions, was not required. In rhodium catalysis, however, 1 equivalent of COD (1,5‐cyclooctadiene) was necessary to induce higher conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 75 publications
0
45
0
1
Order By: Relevance
“…[23] 2,6-Dimethyl substituted substrates 1s and 1t reacted smoothly under the standard conditions to afford the six-member silacycles 3a and 3b in high yields (Figure 3a). When there is acompeting C(sp 2 )ÀH bond such as in substrate 1u,s ilyation of both types of C À H bonds were observed and the C(sp 2 ) À Hb ond silylation product is slightly favoured (Figure 3b).…”
Section: Angewandte Chemiementioning
confidence: 97%
“…[23] 2,6-Dimethyl substituted substrates 1s and 1t reacted smoothly under the standard conditions to afford the six-member silacycles 3a and 3b in high yields (Figure 3a). When there is acompeting C(sp 2 )ÀH bond such as in substrate 1u,s ilyation of both types of C À H bonds were observed and the C(sp 2 ) À Hb ond silylation product is slightly favoured (Figure 3b).…”
Section: Angewandte Chemiementioning
confidence: 97%
“…Using pyridine‐based directing groups, Sato et al. reported that dehydrogenative silylation occurred without any hydrogen acceptors under iridium catalysis ,. More recently, t BuOK‐catalyzed radical silylation of C−H bonds of heterocycles was reported by Stoltz and Grubbs et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the success of the aromatic C(sp 2 )−H silylation, examples of the intermolecular silylation of aliphatic C(sp 3 )−H bonds, to our knowledge, are still rare to date (Scheme ). Since the pioneering work on benzylic C(sp 3 )−H silylation by Kakiuchi and co‐workers, the C(sp 3 )−H silylation of methylboranes and that of methylamines have been reported by others. That is, the examples of directed C(sp 3 )−H silylation have hitherto been limited to cases where there are additional activations by α‐position atoms.…”
Section: Methodsmentioning
confidence: 99%